1999
DOI: 10.1093/bja/83.3.372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on isoflurane requirements in healthy volunteers. 1: Pharmacodynamic and pharmacokinetic interactions

Abstract: Dexmedetomidine is a highly selective alpha 2-adrenoceptor agonist with anaesthetic-sparing effects. We have determined the pharmacodynamic and pharmacokinetic interactions between dexmedetomidine and isoflurane in volunteers. Nine male subjects were allocated randomly to receive isoflurane anaesthesia preceded by infusion of dexmedetomidine on three separate occasions, 2 weeks apart. Dexmedetomidine target plasma concentrations were 0.0 (placebo), 0.3 ng ml-1 (low-dex) and 0.6 ng ml-1 (high-dex). End-tidal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
100
2
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 24 publications
8
100
2
5
Order By: Relevance
“…These fi ndings confi rm with a previous study which showed that use of DEX reduces requirement of inhalational anesthetics [7,8]. The probable mechanism of reducing blood pressure by DEX is attributed to stimulation of peripheral alpha 2 adrenoceptors of vascular smooth muscle .This results in decrease in blood pressure and heart rate secondary to inhibition of central sympathetic outfl ow.…”
supporting
confidence: 89%
“…These fi ndings confi rm with a previous study which showed that use of DEX reduces requirement of inhalational anesthetics [7,8]. The probable mechanism of reducing blood pressure by DEX is attributed to stimulation of peripheral alpha 2 adrenoceptors of vascular smooth muscle .This results in decrease in blood pressure and heart rate secondary to inhibition of central sympathetic outfl ow.…”
supporting
confidence: 89%
“…Kahn et al [11] showed a left shift in isoflurane dose±response curves in volunteers receiving an infusion of dexmedetomidine. Dexmedetomidine 0.35 ng.ml 21 decreased isoflurane requirements to prevent movement in response to a noxious stimulus by 35%; dexmedetomidine 0.75 ng.ml 21 decreased isoflurane requirements by < 50% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Kahn et al [11] showed a left shift in isoflurane dose±response curves in volunteers receiving an infusion of dexmedetomidine. Dexmedetomidine 0.35 ng.ml 21 decreased isoflurane requirements to prevent movement in response to a noxious stimulus by 35%; dexmedetomidine 0.75 ng.ml 21 decreased isoflurane requirements by < 50% [11]. Fragen & Fitzgerald [12] used dexmedetomidine infusions to produce target blood concentrations of 0.3 ng.ml 21 and 0.6 ng.ml 21 in adult patients, the response to surgical stimulus was assessed; sevoflurane MAC was reduced by 17% in the high-dose dexmedetomidine group only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations